High-quality targeted temperature management combined with decompressive craniectomy in patients with poor-grade aneurysmal subarachnoid hemorrhage: a secondary analysis of a multicenter prospective study - Liu, Yang; Han, Bingsha; Li, Yanru; Ren, Zhiqiang; Chen, Yong; Zhang, Ming; Li, Jiao; Wang, Jv; Yang, Fan; Xu, Mengyuan; Zhang, Jiaqi; Zhang, Pengzhao; et al. (Frontiers in Neurology, 2025)
BackgroundThe effect of targeted temperature management (TTM) combined with decompressive craniectomy (DC) on poor-grade aneurysmal subarachnoid hemorrhage (aSAH) has not been previously addressed in the literature. This study aims to investigate the therapeutic outcomes of the combination of TTM and DC in patients with poor-grade aSAH.MethodsThis study represents a secondary analysis of the Multicenter Clinical Research on Targeted Temperature Management of Poor-grade Aneurysmal Subarachnoid Hemorrhage (High-Quality TTM for PaSAH), a multicenter prospective study conducted in China. The High-Quality TTM for PaSAH study enrolled patients aged 18 years and older who were transported to the intensive care units (ICU) of three tertiary care hospitals in China between April 2022 and April 2024. Among these patients, those who underwent DC were included in the present analysis. Patients were divided into two groups: the DC-alone group and the TTM combined with the DC (TTM-DC) group. The DC-alone group maintained normothermia. The TTM-DC group used automated devices with a temperature feedback system (TFS). TTM was initiated with core temperatures between 36°C-37°C immediately after diagnosing poor-grade aSAH, and concurrent emergency aneurysm repair. This was followed by a rapid induction to 34°C-35°C, maintained for a minimum of 72 h. Subsequently, a slow rewarming process reached 36°C-37°C, which was maintained for at least 48 h. Primary outcomes were evaluated using the Modified Rankin Scale (mRS) score at 3 months. Secondary outcomes included the Glasgow Coma Scale (GCS) at discharge, ICU stay duration, length of hospitalization, proportion of external ventricular drainage (EVD), mechanical ventilation time, tracheostomy, midline shift, hydrocephalus, and delayed cerebral ischemia (DCI) on the 7th day. Safety outcomes comprised the incidence of pneumonia, myocardial infarction, stress hyperglycemia, thrombocytopenia, acute liver injury, hypokalemia, hypoproteinemia, and death at 90 days.ResultsOf the 141 patients enrolled in the High-Quality TTM for PaSAH study, 43 (25 in the TTM-DC group and 18 in the DC-alone group) were eligible for this secondary analysis. The TTM-DC group had a higher proportion of favorable outcomes (mRS 0–3: 56% vs. 22%, aOR 5.97, 95%CI 0.96–52.2, p = 0.071). After propensity score matching, the TTM combined with DC improved favorable outcome at 3 months (mRS 0–3: 61% vs. 22%, OR 5.50, 95%CI 1.36–26.3, p = 0.022). In addition, the TTM-DC group increased GCS score at discharge compared with the DC-alone group (9 vs. 3, β 2.58, 95%CI 0.32–4.84, p = 0.032). The incidence of safety outcomes was not increased in the TTM-DC group.ConclusionTTM combined with DC can improve clinical conditions at discharge and ameliorate short-term neurological outcomes in poor-grade aSAH patients. TTM should be considered one of the main treatments for poor-grade aSAH patients who underwent DC.